Pengaruh Pajak Daerah, Retribusi Daerah dan Dana Alokasi Khusus Terhadap Belanja Modal pada Kabupaten/Kota Provinsi Bali - Nurina Zhafira; Enan Trivansyah Sastri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The COVID-19 pandemic has brought changes to the world including Indonesia with various challenges and even presents various new policies, causing various impacts, one of which is the impact on the economic sector. This study aims to determine the effect of local taxes, local levies and special allocation funds on capital expenditure. This study uses a quantitative method with a research population of 45 data on the realization of district and city APBDs in Bali Province in 2017-2021. The number of samples obtained using the saturated sampling technique is 9 districts and cities with observations for 5 years with the period 2017-2021. The data collection techniques in this research are literature study and documentation study. The test tool used to test the data is the panel data regression analysis test using Eviews version 12. A series of tests conducted produces data that can prove that partially local taxes and local retribution have a significant and positive effect, while special allocation funds have no effect on capital expenditure. While simultaneously local taxes, local levies and special allocation funds affect capital expenditure.